2015
DOI: 10.1177/2374289515616972
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts in Head and Neck Squamous Cell Carcinoma Associated With Perineural Invasion Have High-Level Nuclear Yes-Associated Protein (YAP) Expression

Abstract: We retrospectively studied the expression of Yes-associated protein (YAP) using immunohistochemical staining in 10 cases of head and neck squamous cell carcinoma with associated perineural invasion. We find that fibroblasts in areas associated with perineural invasion show higher levels of nuclear YAP compared to fibroblasts in the stroma of normal mucosa, with a median cell count of 35.4 per high-power field in the former and 3.9 in the latter. No differences were observed between the expression of YAP phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…4 . Accordingly, levels of nuclear YAP/TAZ in fibroblasts associated with perineural invasion of HNSCC were higher than those in the stroma of normal mucosa 175 . YAP expression was elevated at the invasive front of HNSCC tumours 176 and also as a consequence of PIK3CA overexpression 177 .…”
Section: Ferroptosismentioning
confidence: 86%
“…4 . Accordingly, levels of nuclear YAP/TAZ in fibroblasts associated with perineural invasion of HNSCC were higher than those in the stroma of normal mucosa 175 . YAP expression was elevated at the invasive front of HNSCC tumours 176 and also as a consequence of PIK3CA overexpression 177 .…”
Section: Ferroptosismentioning
confidence: 86%
“…To perform a preliminary analysis of the role of non-malignant cells in PNI, we evaluated the expression levels of the genes in the key coexpression module, especially the hub genes. We found that these genes were mainly enriched in fibroblasts, an important component of the tumor stroma that contributes to the shaping of the ECM, the metabolic and immune reprogramming of the TME, and the release of growth factors that promote tumor growth and invasion (39, 40). Interestingly, cancer-associated fibroblasts (CAFs) have been found to be in close proximity to p-EMT cells in the surrounding TME.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of increased cytoplasmic pYAP is similar to previous studies conducted by Cao et al [ 25 ] and Yeo et al [ 24 ], which found higher cytoplasmic pYAP expression in an early or lower histological grade of breast cancer and esophageal squamous cell carcinoma (ESCC), respectively. Additionally, increased cytoplasmic pYAP expression was also found in the cancer-associated fibroblast (CAFs) and tumor cells of head and neck squamous cell carcinoma [ 60 ].…”
Section: Discussionmentioning
confidence: 99%